1995
DOI: 10.1093/oxfordjournals.eurheartj.a060833
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen in the offspring of men with premature coronary artery disease

Abstract: We examined whether the levels of fibrinogen are elevated in the offspring of middle-aged coronary patients. One hundred and seventy-six young subjects were divided into two groups. Group A consisted of 100 children and youngsters (mean age 17 +/- 6 years) whose fathers had sustained a myocardial infarction under the age 55 years without associated history of diabetes mellitus or hypertension. Seventy-six healthy young subjects (mean age 18 +/- 5 years) matched for gender, dietary and smoking habits without fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the study, an increased concentration of FB was not found for children with a positive FH. However, data from the literature indicate a higher concentration of FB in children with a FH of premature atherosclerosis, suggesting that elevated FB may be an important marker for risk of cardiac insufficiency in children with a normal lipid profile [23].…”
Section: Discussionmentioning
confidence: 99%
“…In the study, an increased concentration of FB was not found for children with a positive FH. However, data from the literature indicate a higher concentration of FB in children with a FH of premature atherosclerosis, suggesting that elevated FB may be an important marker for risk of cardiac insufficiency in children with a normal lipid profile [23].…”
Section: Discussionmentioning
confidence: 99%
“…Prothrombin fragment 1 2 elevation has been demonstrated for at least 6 months following an acute coronary event (21), but it has been suggested that the increased risk of future coronary thrombosis in patients with increased FBG or C-reactive protein may be due to an inflammatory component to atherosclerosis in those prone to plaque rupture (34). Furthermore, increased FBG in individuals may be genetically determined (29).…”
Section: Scand Cardiovasc J 32mentioning
confidence: 99%
“…Elevated fibrinogen concentrations have been reported in the healthy members of families in which coronary disease has occurred prematurely. 15,16 Given the association between fibrinogen and insulin resistance, 17 increased levels of fibrinogen may act as a potential confounder in studies of the insulin resistance syndrome in such families.…”
mentioning
confidence: 99%